Characteristics of Using Feed Impact on Tilapia (Oreochromis niloticus) Culture Using a Dynamics System Approach - Ade Kurniawan; Abdul Gani; Endang Muhammad; George M. Numberi; Endang Y. Papare; Asti; Otto Sada (Journal of Aquaculture and Fish Health, 2023)
Feed was the most important part in aquaculture. Not only affecting growth, but the feed also impacted the cultivation environment. Poor feeding management in the use of feed will have a negative impact on the cultivation process. The purpose of the research was to create a dynamic system model. In the model a systemized algorithm was structured that would assist cultivators in carrying out aquaculture activities and with this model, problems that occurred were immediately resolved. The dynamic system model was the method used in this research. This model was used to determine the optimization of feed use based on several variables that support the process of using the feed. In this research, the production of Oreochromis niloticus was 14 kg, the amount of feed used was 10 kg, which affects the increase in the amount of organic matter, which was 3626.4 g (total feces + uneaten feed) in 65 days cultivation period. The result showed that the total feed was connected with organic waste, namely total N, total P, total feces, and total uneaten feed. The results obtained from this research were then poured into a dynamic system and the results were found, namely the relationship between feeding and organic waste, namely linear or perpendicular. The design of this dynamic system model was expected to enable tilapia cultivators to develop aquaculture businesses that were more environmentally friendly, effective, and efficient.